The Impact of Sustainability Reports, Sustainability Accounting, and Environmental Innovation on the Achievement of the Sustainable Development Goals (SDGs): Empirical Evidence on Consumer Goods Companies in the Food and Beverage Sub-Sector in Indonesia - Dewi, Kadek Goldina Puteri; Martini, Ni Putu Riski; Ratnasari, Ni Made Devi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to examine the effect of sustainability reporting, sustainability accounting, and environmental innovation on the achievement of Sustainable Development Goals (SDGs) at the corporate level. The research focuses on consumer goods companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2022. Using a quantitative approach, this study employs secondary data obtained from annual reports and sustainability reports. The sample is selected through purposive sampling, resulting in panel data observations analyzed using panel data regression. The dependent variable is SDGs achievement, measured through an SDGs disclosure index based on Global Reporting Initiative (GRI) indicators with an emphasis on environmental and waste management aspects. The independent variables include sustainability reporting quality, sustainability accounting practices measured through environmental cost and waste management investment disclosures, and environmental innovation proxied by disclosures of environmentally friendly products and processes. The results of the fixed effect model indicate that sustainability reporting, sustainability accounting, and environmental innovation have a positive and significant effect on corporate SDGs achievement. Sustainability accounting demonstrates the strongest influence, highlighting the importance of internal measurement and recognition of environmental costs in supporting sustainable development. These findings suggest that achieving SDGs in the food and beverage industry requires an integrated sustainability approach that combines transparent reporting, robust sustainability accounting systems, and continuous environmental innovation.